STUDI PELAYANAN KESEJAHTERAAN LANJUT USIA PADA UPTD PANTI SOSIAL TRESNA WERDHA ( PSTW ) MARGA RAHAYU DINAS SOSIAL KALIMANTAN UTARA DI KABUPATEN BULUNGAN - Irsyad Sudirman; Iskandar, Iskandar (Bajang Institute, 2024)
The purpose of this study was to determine and describe the services to the elderly in Tresna Elderly UPTD Social Institution of Highways Rahayu Bulungan as well as to identify factors supporting and servicing the elderly Elderly Tresna UPTD Social Institution of Highways Rahayu at Bulungan. This type of research is descriptive qualitative research is the collection of data obtained in the form of primary and secondary data, the data obtained directly from the sources (informants) with a research focus include Procedures, Cost of Services, Program Services, Facilities and Infrastructure, as well as Supporting factors and Services inhibitors elderly On Tresna elderly UPTD Social Institution of Highways Rahayu. In the determination of Key Informants researchers using purposive sampling technique in which information or data collected by selecting informants who are considered competent to be a source of data, including the Head of Social Institution Tresna Elderly UPTD Marga Rahayu and staff as complementary informants and other informers are the elderly who stay at home as well as the families who came to visit by using Accidental Sampling techniques. From the results of this research is that the services provided to older persons displaced in meeting their needs has been carried out based on the number of human resources, facilities and infrastructure, as well as the budget available, it can be seen that the government's efforts to cope with the number of abandoned elderly who have not received perceived welfare still lacking. Although the number of elderly people who get welfare services that are in UPTD Tresna Elderly Social Institution of Highways Rahayu based on available capacity, but significant in reducing the number of neglect of elderly who are in the province of North Borneo.